Optimasi Formula Sedian Lotion Ekstrak Etanol 70% Daun Kersen (Muntingia Calabura L.) - Aristha Novyra Putri; Anasdi Nazar; Ika Maulida Nurrahma (Universitas Borneo Lestari, 2022)
Kersen leaves (Muntinga Calabura L.) is a plant that has antioxidant activity with a 6.8249 µg / mL IC50 value with flavonoid and phenol compounds. So that it can be used as an active ingredient in lotion. This study aimed to determine the effect of stearic acid emulsifiers and triethanolamine on the physical characteristics of the lotion and to find out the optimum formula for the ethanol extract of Kersen leaves (Muntingia calabura L.) by using the factorial design method The results showed that the combined value of stearic acid and triethanolamine produced a pH (-0.0717) response, (+4556.67) viscosity, (-0.2750) spreadability and (+0.0045) adhesion. Based on these data it could be concluded that the combination of stearic acid and triethanolamine could increase viscosity and adhesion. The combination of stearic acid with triethanolamine could reduce the pH response and spreadability. So that the optimum formula for lotion with stearic acid and triethanolamine concentrations was 17.63% and 3.29%, respectively.